High-Stakes Institutional Translation: Establishing North America’s First Government-sanctioned Supervised Injection Site - Lawrence, Thomas B. (Academy of Management Journal, 2017)
Around the world, potentially effective responses to serious social problems are left untried because those responses are politically, culturally, or morally problematic in affected communities. I describe the process through which communities import such practices as “high-stakes institutional translation.” Drawing on a study of North America’s first supervised injection site for users of illegal drugs, I propose a process model of high-stakes institutional translation that involves a triggering period of public expressions of intense emotion, followed by waves of translations in which the controversial practice is constructed in discursive and material terms many times over.